Experimental and numerical study on the model of hybrid fiber phase change concrete frozen shaft wall. - Dongwei Li; Zhiwen Jia; Zecheng Wang; Kaixi Xue; Zhenhua Wang; Fang Fang (PLoS ONE, 2024)
In this study, phase change materials (PCMs) were innovatively incorporated into hybrid fiber concrete. The properties of PCMs, which absorb and release heat during phase transitions, enable the concrete to actively respond to complex and varying temperature environments. This integration reduces the internal temperature differentials within the concrete, thereby preventing temperature-induced cracks in deep wellbore structures. Through the temperature control model test of the frozen shaft wall, it can be seen that the hybrid fiber phase change concrete (HFPCC) significantly reduces the internal temperature difference, and the maximum temperature difference along the radial direction is 35.84% lower than that of benchmark concrete (BC). The numerical simulation results indicate that a moderate phase transition temperature should be selected in engineering. The phase change temperature should not be close to the ambient temperature and peak temperature. The peak temperature can be reduced by 9.32% and the maximum radial temperature difference can be reduced by 30.89% by selecting an appropriate phase change temperature. The peak temperature and radial maximum temperature difference are both proportional to the latent heat of phase change. The temperature control performance of phase change concrete can be further improved by increasing the latent heat of phase change materials.